School lives of adolescent school students living with chronic physical health conditions: a qualitative evidence synthesis. Issue 3 (2nd December 2022) - Spencer, Bethan K C; Wright, Judy; Flemming, Kate; Cottrell, David; Pini, Simon
Abstract : Objective: Assess the existing evidence base in order to synthesise the current qualitative findings for the impact of chronic health conditions on the school lives of young people. Design: Qualitative evidence synthesis using thematic synthesis. Patients: Young people aged 11–18 years with a chronic health condition from one of the following groups: oncology, cystic fibrosis, diabetes, asthma, rheumatology, neuromuscular, colorectal, chronic pain, allergies and dermatology. Outcome measure: Qualitative findings and discussions present in included studies formed the data for the thematic synthesis. Results: From a search identifying 19 311 records, a sample of 35 papers were included. The included papers represented 15 countries and primarily employed interviews as part of data collection. Thematic synthesis resulted in six themes: 'keeping up/catching up/missing out/looking forward'; 'identity'; 'relationship with peers'; 'normality and difference'; 'autonomy'; 'relationships with staff'. Conclusions: Thematic synthesis highlighted the commonalities, rather than divergence, of issues for young people across different chronic conditions. Policies need to be based on the experiences of the people they aim to provide for, and while attendance and attainment remain important, there is clearly more that needs to be considered when gathering data, designing interventions and developing policies to support this population. It may also be advisable for clinical professionals to include the broader psychosocial aspects of school life in discussions and plans to support young people with long-term conditions. PROSPERO registration number: CRD42021278153.